1991
DOI: 10.1111/j.1365-3024.1991.tb00544.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of immune serum and complement on the in vitro phagocytosis of Babesia rodhaini

Abstract: The effect of immune serum and complement on the in vitro phagocytosis of Babesia rodhaini was investigated. Infected erythrocytes and parasites released from erythrocytes by lysis were phagocytosed by mouse peritoneal macrophages in vitro when the infected erythrocytes or parasites were exposed to hyperimmune B. rodhaini serum. Complement, in the presence of immune serum, did not reproducibly enhance phagocytosis of infected erythrocytes or parasites alone. When adjusted for its effect on normal erythrocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…These antibodies also caused phagocytosis of infected erythrocytes by cultured bovine monocytes. A positive correlation between the opsonin titer and protective activity against Babesia rodhaini in rats occurs (23). Studies of B. bovis (9,10,15), Babesia equi (13), and Babesia canis (28) infections indicate that phagocytosis of infected erythrocytes by peripheral blood leukocytes is involved in the resolution of infections.…”
Section: Discussionmentioning
confidence: 99%
“…These antibodies also caused phagocytosis of infected erythrocytes by cultured bovine monocytes. A positive correlation between the opsonin titer and protective activity against Babesia rodhaini in rats occurs (23). Studies of B. bovis (9,10,15), Babesia equi (13), and Babesia canis (28) infections indicate that phagocytosis of infected erythrocytes by peripheral blood leukocytes is involved in the resolution of infections.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, it has been observed that several components of the complement pathway are essential in the invasion of erythrocytes by B. rodhaini (31). Also, in a study in which complement was used to promote macrophage phagocytosis of B. rodhaini merozoites, the unexpected finding was that the presence of complement inhibited phagocytosis of the pathogen (157).…”
Section: Host Immune Responsementioning
confidence: 96%
“…(37) showed that the complement, in the presence of an immune serum, does not reproducibly enhance the phagocytosis of infected erythrocytes with B. rodhaini or parasites alone in vitro . The depletion of serum C3 does not affect the course of B. rodhaini in BALB/C mice (37). Likewise, the complement does not have a role in the entry of B. bovis into the RBC in vitro (39).…”
Section: Research Notementioning
confidence: 99%